2019
DOI: 10.1115/1.4045024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Swirl on the Stabilization of Non-Premixed Oxygen-Enriched Flames Above Coaxial Injectors

Abstract: An experimental study is carried out to analyze the effects of swirl on the structure and stabilization of methane non-premixed oxygen-enriched flames above a coaxial injector in which the two streams are eventually swirled. The mean position of the flame and the liftoff height above the injector lips are investigated with OH* chemiluminescence images. The oxygen enrichment, the momentum flux ratio between the two coflows, the swirl level inside the central jet, and the swirl level in the annular jet are varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…For nonswirling central fuel jet, it is known that the impulsion ratio J = ρeu 2 e /(ρiu 2 i ) between the external swirled oxidizer and internal fuel streams is the main parameter controlling flame stabilization [16]. When the fuel is swirled, a high value of the impulsion ratio J was found to be a necessary condition to lift CH4 oxy- flames in [14,15], but the external velocity ue was not varied in these studies. The detailed physical mechanisms by which the flame anchors or detaches from the burner lips were also not elucidated.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…For nonswirling central fuel jet, it is known that the impulsion ratio J = ρeu 2 e /(ρiu 2 i ) between the external swirled oxidizer and internal fuel streams is the main parameter controlling flame stabilization [16]. When the fuel is swirled, a high value of the impulsion ratio J was found to be a necessary condition to lift CH4 oxy- flames in [14,15], but the external velocity ue was not varied in these studies. The detailed physical mechanisms by which the flame anchors or detaches from the burner lips were also not elucidated.…”
Section: Introductionmentioning
confidence: 88%
“…Mixing between two coaxial jets is improved by adding swirl to the central fuel stream and more specifically for light gases as hydrogen [13]. Recently, Degeneve et al [14,15] showed that swirling the fuel helps lifting the flame from the fuel injector nozzle in a configuration with swirled annular and internal channels flush mounted with the combustion chamber backplane. For nonswirling central fuel jet, it is known that the impulsion ratio J = ρeu 2 e /(ρiu 2 i ) between the external swirled oxidizer and internal fuel streams is the main parameter controlling flame stabilization [16].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 indicates that the bulk velocity u e barely changes when methane is removed from the external channel, but the global equivalence ratio drops from φ = 0.75 for methane/air Ref operation to φ = 0.62 for hydrogen/air PH100 operation. The momentum ratio J, which is an important parameter controlling flame lift-off above co-axial injectors [17,20] decreases as the fraction of H 2 increases.…”
Section: Effect Of Inner Swirl and Recessmentioning
confidence: 99%
“…For this baseline configuration obtained for u e0 = 24 m/s and φ 0 = 0.75, Fig. 3 shows that all Following [19,20,21], the impact of swirling the fuel in the central lance is now investigated for configuration S of the burner with an internal swirling vane S i 0 but no recess z i = 0 of the hydrogen lance. The top row in Fig.…”
Section: Effect Of Inner Swirl and Recessmentioning
confidence: 99%
See 1 more Smart Citation